2017
DOI: 10.12659/msm.903440
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Treatment of Acute Unstable Distal Clavicle Fractures Using Anatomical Locking Plates with Versus without Additional Suture Anchor Fixation

Abstract: BackgroundSurgical managements were recommended for unstable distal clavicle fracture owing to the high incidence of nonunion. The present study compared the efficacy of anatomical locking plate with versus without additional suture anchor fixation for the treatment of unstable Neer type II distal clavicle fractures.Material/MethodsBetween January 2013 to January 2015, 28 consecutive patients with unstable Neer type II fractures were treated by using anatomical locking plate with or without additional suture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
0
23
0
1
Order By: Relevance
“… 16 , 30 , 29 , 31 In recent years, there have been an increasing number of reports on the addition of C-C ligament augmentation using a suture anchor or suture button to plate fixation for unstable distal clavicle fractures. 8 , 27 , 33 , 34 While it had been reported that the addition of C-C ligament augmentation provided better functional outcomes, 8 , 33 a report indicated comparable outcomes after plate fixation with and without C-C ligament augmentation 27 ; therefore, the benefit of using additional C-C ligament augmentation compared with plate fixation alone is controversial. In addition, there are concerns about complications owing to the addition of C-C ligament augmentation, such as clavicle fracture 1 , 5 , 7 , 14 , 15 and coracoid process fracture 3 , 17 , 35 at the suture hole and brachial plexus injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 30 , 29 , 31 In recent years, there have been an increasing number of reports on the addition of C-C ligament augmentation using a suture anchor or suture button to plate fixation for unstable distal clavicle fractures. 8 , 27 , 33 , 34 While it had been reported that the addition of C-C ligament augmentation provided better functional outcomes, 8 , 33 a report indicated comparable outcomes after plate fixation with and without C-C ligament augmentation 27 ; therefore, the benefit of using additional C-C ligament augmentation compared with plate fixation alone is controversial. In addition, there are concerns about complications owing to the addition of C-C ligament augmentation, such as clavicle fracture 1 , 5 , 7 , 14 , 15 and coracoid process fracture 3 , 17 , 35 at the suture hole and brachial plexus injury.…”
Section: Discussionmentioning
confidence: 99%
“…Plate fixation has recently become an established surgical treatment for distal clavicle fractures and yields satisfactory outcomes. 8 , 9 , 13 , 18 However, even with stable plate fixation, C-C separation can remain postoperatively because of the functional loss of the integrity of the C-C ligament and may affect the likelihood of postoperative complications. Although there have been studies that focused on the presence or absence of bone union, residual C-C separation after osteosynthesis for an unstable distal clavicle fracture has rarely been discussed.…”
mentioning
confidence: 99%
“…Plate fixation for distal clavicular fractures has been reported to achieve satisfactory bone union rates [8][9][10][11][12][13][14]; however, one of the important clinical problems is the rate of postoperative complications. While hook plates showed good outcomes for fractures with comminuted distal bone fragments, various complications, such as peri-implant fracture, dislocation, and limited range of motion were reported [6,10,15].…”
Section: Introductionmentioning
confidence: 99%
“…The baseline characteristics of the included studies are presented in Table 1 . Of the 41 included studies, 28 [ 15 , 20 , 33 36 , 39 , 42 , 44 – 48 , 53 – 68 ] were from China, 3 [ 14 , 21 , 52 ] were from the USA, 3 [ 37 , 38 , 43 ] were from Germany, 2 [ 40 , 41 ] were from Finland and 1 each was from Korea [ 51 ], Australia [ 33 ], Turkey [ 16 ], Morocco [ 49 ], and the Netherlands [ 50 ]. There were 1969 Neer type II (1642/1969, 83.4%; type II B, 709/1969, 36%) and unclear type (type II or type V, 327/1969, 16.6%) distal clavicle fractures that were fixed with HP (hook plate, 923/1969, 46.9%), LCP (locking compression plate, 384/1969, 19.5%), CC (coracoclavicular reconstruction, 255/1969, 13.0%), LCP + CC (combination of locking compression plate and coracoclavicular reconstruction, 260/1969, 13.2%), KWTB (Kirshner wire and tension band, 123/1969, 6.2%), KWTB + CC (combination of Kirshner wire and tension band and coracoclavicular reconstruction, 10/1969, 0.5%), or KW (Kirshner wire, 14/1969, 0.7%).…”
Section: Resultsmentioning
confidence: 99%